Teens in the Philippines - Jason Maurice Skog (Minneapolis, MN, United States COMPASS POINT BOOKS, 2009)
Spread across 7,107 islands, teens in the Philippines live in a country that mixes old-fashioned ways of life with the newest technology. Teens line up to see the newest movie with their friends, work an extra job for spending money, and study hard to be successful in school. But nothing is more important than family, and Filipino teens celebrate birthdays, holidays, festivals, and other celebrations surrounded by loved ones. Teens in the Philippines is part of Global Connections, a series that uncovers the challenges, pastimes, and customs of teens around the world.
Keywords: Non Fiction